Cooptation of ENGOs or Treadmill of Production? Advocacy Coalitions and Climate Change Policy in Finland. - Gronow, Antti; Ylä‐Anttila, Tuomas (Policy Studies Journal, 2019)
Corporatist Nordic welfare states are largely thought to have exemplary environmental policies. Finland, however, was labeled "a failing ecostate" by a recent study owing to its weak climate change policy. Why is Finland different? We use data from a survey of organizations belonging to the Finnish climate change policy network to investigate two alternative explanations related to policy networks. According to the Cooptation Thesis, inclusive corporatist polities, where environmental NGOs (ENGOs) have support from and access to the state, formulate less ambitious policies because environmentalists moderate their views to secure state funding and political access. Second, according to the Treadmill of Production Theory, the decisive feature of Nordic corporatism with regard to environmental policy is the tripartite system linking business interests, labor unions, and the state in a coalition that prioritizes economic over ecological values. The results indicate that the ENGO Coalition is the least influential, least resourceful, smallest, least linked to the others, and not particularly moderate. The Treadmill Coalition is the most influential, most resourceful, second largest, well linked to the state, and least ecological in its beliefs. Thus, of the two policy network explanations, the dominance of the Treadmill Coalition rather than cooptation of ENGOs gets support.